2023
DOI: 10.1051/e3sconf/202336504024
|View full text |Cite
|
Sign up to set email alerts
|

Development of new pole-changing winding for lifting and transport mechanisms

Abstract: In many industries, lifting and transport machines are used, particularly cranes, conveyors, and hoists. Taking into account their wide prevalence and large installed capacity, as well as the complexity of the operating mode, special attention is paid to the creation of new energy- and resource-saving electric drives that facilitate the start-up process and ensure accurate stopping of highly inertial lifting and transport mechanisms. In this direction, one of the priority tasks is the development of two-speed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 12 publications
0
26
0
Order By: Relevance
“…It should be noted that the task of designing a twospeed motor with one winding is a complex process and can be compared with the simultaneous design of two single-speed motors that have interconnected parameters and cannot be changed unilaterally [14,18].…”
Section: The Current State Of the Investigated Problemmentioning
confidence: 99%
“…It should be noted that the task of designing a twospeed motor with one winding is a complex process and can be compared with the simultaneous design of two single-speed motors that have interconnected parameters and cannot be changed unilaterally [14,18].…”
Section: The Current State Of the Investigated Problemmentioning
confidence: 99%
“…When resistance welding, spot welding is the most economical, therefore expanding the use of spot welding provides greater energy savings [16][17][18][19][20].…”
Section: Electrothermal Processes (High Temperature Technologies)mentioning
confidence: 99%
“…-A groundbreaking study from the University of Stuttgart found that students who underwent training in VR labs outshone their peers by 20% during practical skill evaluations [27][28][29][30][31][32].…”
Section: Statistics and Impactmentioning
confidence: 99%